Faktor penentu matlamat kerjaya sebagai akauntan bertauliah dalam kalangan pelajar perakaunan di Malaysia - Mohd Raime, Ramlan (2020)
Malaysia faces a serious shortage of qualified accountants as only a small number of accounting graduates choose to pursue a career in the accounting profession. This situation is alarming as the current number of accounting professionals is just 36,976, far from the target of 60,000 accountants as required in line with the implementation of the Economic Transformation Program (ETP) and National Transformation 50 (NT50). Previous reports and studies have shown that the main cause of this problem is due to low interest among accounting students to venture into the accounting profession. Based on Social Cognitive Career Theory (SCCT), the objectives of the study are to determine whether personality traits, learning experiences, self-efficacy, outcome expectation, and interest, could explain the career goals of a student as a Chartered Accountant. Survey and questionnaire methods are used for data collection purposes. Structural Equation Modeling (SEM) analysis is performed on 376 selected respondents via convenient sampling. The results of the study show that the construct of personality traits of neuroticism, openness, and agreeableness along with interest have a significant relationship with career goals. The analysis also indicates that the construct of interest had a significant mediating effect on the relationship between self-efficacy, outcome expectation, and career goals. Furthermore, the construct of learning experience also significantly affects self-efficacy. These findings are in line with the proposed theory and consistent with previous studies in accounting as well as other areas. The findings of this study provide concrete recommendations to the accounting professional body, Ministry of Higher Education (MOHE) and accounting schools, to formulate more effective strategies to attract more individuals to join the accounting profession.